Investigating dusty red supergiant outflows in Westerlund 1 with 3D hydrodynamic simulations - Larkin, Cormac; Mackey, J.; Haworth, T. J.; Sander, A. a. C. (Astronomy and astrophysics, 2025)
Context. Recent JWST observations towards Westerlund 1 have revealed extensive nebular emission associated with the cluster. Given the age of the region and the proximity of that material to massive stars, it cannot be primordial star-forming gas and the origin is uncertain. Aims. We aim to determine whether the nebular emission in Westerlund 1 is due to ablation flows from red supergiant (RSG) stars embedded in the cluster wind driven by the Wolf-Rayet stars in the cluster core. We also aim to explore the efficiency of mass loading for the RSG wind in this scenario. Methods. We used 3D hydrodynamic simulations with the PION code to study the interaction between the cluster and RSG winds. We compared our simulations with the JWST observations by generating synthetic dust-emission maps.Results. We find that the ablation flow morphology - which shows clumps and instabilities - is consistent with the observations towards Westerlund 1. Synthetic observations at 11 µm predict fluxes in the ablation flow of ~1000-6000 MJy ster-1, which is consistent with the unsaturated components of the JWST F1130W observations in the vicinity of the RSGs in the region. This good agreement is achieved without any consideration of polycyclic aromatic hydrocarbons (PAHs), which have a known 11.3 µm feature that appears in the F1130W band. This suggests that the environment is not conducive to PAH formation and/or the ablation flow is PAH-depleted by wind and radiation action. Conclusions. Ablation of RSG winds can explain the observed nebulosity in Westerlund 1, at least in the vicinity of the RSGs. Further observations are encouraged to enable detailed studies of these interactions.
Gesehen am 11.12.2025